Modern cookery for private families - Acton, Eliza, 1799-1859 (Salt Lake City, UT : Project Gutenberg, 2023)
"Modern Cookery for Private Families" by Eliza Acton is a cookery book first published in 1845. This groundbreaking work revolutionized recipe writing by introducing exact ingredients, quantities, and cooking times$1 (Ba major departure from previous cookbooks. Praised by culinary writers including Delia Smith and Elizabeth David, it became a bestseller through thirteen editions. The book features everything from fish to puddings, written in Acton's distinctive storytelling style, with practical essays and personal asides that guide cooks through each dish with clarity and charm. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Modern_Cookery_for_Private_Families
Release date is 2023-12-23
Aaron Adrignola and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Cooking, English